Innowacyjność gospodarki w wymiarze współczesnym i w ujęciu historycznym - Drabińska, Danuta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
The paper presents theoretical and practical aspects of knowledge and high technology-based economy. Those aspects relate to economy of innovation, theory of technological gaps, dilemmas of macroeconomic policy based on convergence and absorption processes as well as empirical analysis of those problems. Innovation potential of Poland in international context, the problems of absorption and financial and technological gaps are discussed, quoting the data from the 2010 report on innovativeness of Polish economy. Barriers to innovation for Polish enterprises and the importance of Warsaw in creating the knowledge sector of Polish economy in the context of other Central and Eastern European capitals are also analyzed.